(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
In today’s world, the emphasis is on to move toward the digital driven economy, businesses, and human life. This huge movement towards digitization has resulted in generation of humongous amount of digital content. Managing this digital content is a challenge in it itself. A content management system provides way to handle this data efficiently. CMS are software applications that provide us the capability for easy management and maintainability of this digital content. The number of content management systems have been developed and successfully productionized such as Word press, Joomla, Cascade Server, Wix etc. the paper provides an overview of capabilities of WordPress CMS and various functionalities it offers for digital content management.